The Geo-Politics for Preventing Human Trafficking in Indonesia: A Lesson Learn from Maritime State - Ramadhan, Muhammad Pathan; Sulistyanti, Jihan Syahida (Universitas Negeri Semarang, 2020)
In this modern era, the borders between one country and another began to disappear. The existence of this condition full of freedom facilitates the occurrence of human trafficking. Human trafficking is a very complex problem. Like Indonesia, along with the development of the times, the threat of human trafficking has increased. This paper is intended to analyze how Indonesia deals with Human Trafficking Cases? The paper analyzes the effort of government on multi-sectoral and implementation of laws and regulation on handling the case. The research uses doctrinal legal research with normative legal approach. The research highlighted and illuminated that the swift flow of globalization and the very strategic geographical conditions and with the vast sea area allows Indonesia as an area traversed by international human trafficking routes. To address this problem, for the sake of the safety and comfort of Indonesian citizens, it is necessary to apply a total and integrated problem-solving model, especially in the maritime field.